North Sumatra Economic Growth: an Empirical Study of Unemployment and Poverty Panel Data With an Islamic Economic Review (2021-2023 Period) - Permatasari, Putri Dwi; Tambunan, Khairina; Harahap, Muhammad Ikhsan (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
North Sumatra Province continues to experience economic growth during the 2021–2023 period; however, this growth has not been accompanied by a proportional improvement in social welfare, as indicated by persistently high unemployment and poverty rates across several regencies and cities. Based on secondary data obtained from the Central Bureau of Statistics (BPS) of North Sumatra, these conditions reflect a structural challenge in which economic expansion has not fully translated into productive employment and poverty reduction. This study aims to analyze the influence of unemployment and poverty on economic growth in North Sumatra Province from an Islamic economic perspective.This study employed a quantitative approach with a causal associative design. The data consisted of secondary panel data from 33 regencies/cities in North Sumatra Province during the 2021–2023 period, obtained from the Central Statistics Agency (BPS) and the Financial Services Authority (OJK). Data were analyzed using panel data regression with multiple linear regression techniques, preceded by model selection tests including the Chow test, Hausman test, and Lagrange Multiplier test to determine the most appropriate estimation model. The analysis was conducted using Eviews 13, and the test results indicated that the Common Effect Model (CEM) was the most suitable model for this study.The results show that unemployment has a positive and significant effect on economic growth, while poverty has a negative and significant effect. Simultaneously, both variables significantly influence economic growth with a coefficient of determination of 27.1%. These findings imply that economic growth in North Sumatra has not been fully driven by productive employment, indicating the need for policies that prioritize job quality and labor productivity. Furthermore, poverty alleviation emerges as a key policy instrument to foster inclusive and sustainable economic growth in line with the principles of justice, welfare distribution, and social balance emphasized in Islamic economics.